IL-23 past, present, and future: a roadmap to advancing IL-23 science and therapy - Krueger, James G.; Eyerich, Kilian; Kuchroo, Vijay K.; Ritchlin, Christopher T.; Abreu, Maria T.; Elloso, M. Merle; Fourie, Anne; Fakharzadeh, Steven; Sherlock, Jonathan P.; Yang, Ya-Wen; Cua, Daniel J.; McInnes, Iain B. (Frontiers in Immunology, 2024)
Interleukin (IL)-23, an IL-12 cytokine family member, is a hierarchically dominant regulatory cytokine in a cluster of immune-mediated inflammatory diseases (IMIDs), including psoriasis, psoriatic arthritis, and inflammatory bowel disease. We review IL-23 biology, IL-23 signaling in IMIDs, and the effect of IL-23 inhibition in treating these diseases. We propose studies to advance IL-23 biology and unravel differences in response to anti–IL-23 therapy. Experimental evidence generated from these investigations could establish a novel molecular ontology centered around IL-23–driven diseases, improve upon current approaches to treating IMIDs with IL-23 inhibition, and ultimately facilitate optimal identification of patients and, thereby, outcomes.